Short-term Regulation of Resistin in vivo by Oral Lipid Ingestion and in vitro by Fatty Acid Stimulation - Schmid, A.; Leszczak, S.; Ober, I.; Karrasch, T.; Schäffler, A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background and aim: Dysbalance of pro- and anti-inflammatory adipokines is a hallmark of metabolic syndrome but their nutrition-dependent regulation in healthy individuals is poorly characterized. We investigated pro-inflammatory resistin and anti-inflammatory adiponectin regulation during oral lipid ingestion (OLI) in healthy adults. Response of resistin upon free fatty acid (FFA) stimulation was investigated in 3T3-L1 adipocytes.Material and methods: 100 healthy volunteers underwent OLI. Venous blood was drawn after 0, 2, 4, and 6 hours (h). Subjects were characterized by anthropometric and standard laboratory parameters. Serum concentrations of adiponectin and resistin were measured by enzyme-linked immunosorbent assay (ELISA). Adipocytes were stimulated with FFA and concentrations of adipokines were measured by ELISA.Results: Irrespective of BMI and gender, OLI led to a significant reduction of resistin serum levels in a stepwise manner whereas adiponectin concentrations remained unchanged. There were positive correlations of resistin with waist/hip ratio and visfatin levels, as was calculated by regression analysis. Resistin concentrations were significantly higher in smokers when compared to non-smokers. Adiponectin concentrations were higher in females and in users of hormonal contraception. Adiponectin levels showed a positive correlation with heart rate and HDL cholesterol and a negative correlation with age, waist/hip-ratio, BMI, diastolic/systolic blood pressure, visfatin levels and LDL/HDL-ratio. Resistin secretion was significantly induced by palmitic acid, linoleic acid and oleic acid in adipocytes.Conclusions: OLI is a physiological repressor of systemic resistin release whereas FFA upregulate resistin release in vitro from adipocytes.
Keywords: adipocytokines; dietary lipids; inflammation